Autonomous boat for underwater surveillance - Rashid, Muhammad Mahbubur; Embong, Abd Halim; Hazim, Azizi; Nayen, MD. Julkar; Roy, Rupal (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Generally, an autonomous boat with vision ability faces difficulties in navigation and data processing. In this work, implementation on image processing in underwater environment is implemented using autonomous for surveillance purposes. In this endeavor, the focus will be on analyzing the use of single vision cameras in providing data for research on environmental front underwater and also detecting depth and obstacles for better navigation. The system is able to detect solid objects in underwater and it can provide different information of marine environment using correct algorithm and technique. The result is accurate enough to detect obstacles or objects above and beneath the water taking into account the diffraction of light needed for perfect vision. In this research, OpenCV library is used for digital image processing and color feature analysis rather than MATLAB due to the complexity for real time process. The design structure is mainly based on Pontoon style because it is more stable and reliable especially on the river wave condition. Moreover, additional sensors and actuators are implemented in this project to monitor underwater information for navigation purposes.